Effectiveness of Guided E-Booklet-Based Education on Self Care Behavior and Blood Sugar in Hospital X Bandung - Asriyanti, Asriyanti; Prabawati, Dewi; Wilhelmus, Wilhelmus (Syntax Corporation Indonesia, 2024)
Diabetes mellitus is a metabolic disorder requiring patients to manage and stabilize their condition to prevent complications. Education using e-booklets can facilitate information access and blood sugar control. This study aimed to eval_uate the effectiveness of e-booklet-based education on self-care behavior and blood sugar levels in diabetes mellitus patients. Conducted from June to August 2023 at X Hospital's internist clinic in Bandung, the research employed a quasi-experimental pre-test and post-test design with a control group. The study involved 126 respondents, with 63 in the intervention group and 63 in the control group, selected through purposive sampling. The intervention lasted 4 weeks, covering 8 materials with ongoing monitoring and active participation. Self-care behavior and random blood sugar levels were measured at the beginning and end of the study using the Summary Diabetes Self-Care Activity (SDSCA) questionnaire and blood glucose tests. The Wilcoxon test revealed significant differences in self-care behavior and blood sugar levels before and after the intervention (p < 0.05). The Mann-Whitney test showed significant differences between the intervention and control groups (p < 0.05). Multivariate analysis indicated that age, gender, education, disease duration, and e-booklet-based education accounted for 22.2% of the variance in self-care behavior and 30.6% in blood sugar levels. E-booklet-based education effectively improves self-care behavior and blood sugar control. The study recommends ongoing development and supervision to establish healthy habits and prevent complications.